Analysis of the main results of the scientific research works of the DI «O.M. Marzieiev institute for public health of the NAMS of Ukraine» for 2018-2022 (Environment & Health, 2024)
The Aim - conducting a comparative analysis of the main indicators of the Institute's scientific activity for the period 2018 - 2022.Materials and methods: the analysis was carried out on the basis of the publication activity of the Institute's researches in 2018 – 2022 and the materials of the implementation of the results of research works presented in the Institute's annual reports. The number of the published material of the Institute amounted to more than 1,000 items. Bibliosemantic, analytical and statistical methods were used to process the materials.Research results: the main result of the conducted analysis is the establishment of the most significant results of the Institute's scientific activity for the period 2018-2022:• the Concept of the formation of a strategy for the prevention of defects in the provision of medical care in the domestic health care system was developed, which can be the basis for the formation of an appropriate policy and strategy in the field of quality and safety of medical care in Ukraine;• prognostic trends of changes in children's morbidity were determined; modern approaches to the integral assessment of the health of the child population have been developed to improve the principles of dynamic monitoring of its formation using information technologies;• the system of preventive measures against hypokinesia in urban adolescents is substantiated, based on identified indicators of motor activity, factors affecting children's motor activity;• the medical and ecological problems of assessing the danger to public health of the consequences of climate change related to atmospheric air pollution are prioritized;• the carcinogenic risk from the action of chloroform in drinking water was determined using simplified mathematical formulas;• available technologies for water purification from radionuclides are proposed;Conclusions: The analysis of the main indicators of the Institute's scientific activity for the period 2018 - 2022 made it possible to establish the types of scientific production typical for this field of activity, the reasons for their decrease in certain years of the considered period; areas of their implementation; determine significant results of research works; to confirm the compliance of the chosen topic of research work with the tasks of the National Academy of Sciences of Ukraine and the main recommendations of the WHO in the field of public health.
Keywords: research work; indicators of scientific activity; publication activity; innovation; implementation; effectiveness of scientific research